Assessing the Impact of Leadership and Organizational Culture on the Performance of Personnel and Human Resources Development Agency in Enrekang Regency - Safri Ramadhana; Idayanti Nursyamsi; Nurjannah Hamid (Cita konsultindo, 2023)
The implementation of change often requires effective leadership as an important first step, rather than verbal assurances. Therefore, this study aims to determine the quality or ability of Human Resources to carry out their duties and functions at the Personnel and Human Resources Development Agency in the Enrekang Regency. The study procedures were carried out using a quantitative method with a saturated sampling approach, involving 36 participants. The results showed that: 1) Leadership had no significant influence on performance of the Personnel and Human Resources Development Agency in the Enrekang Regency, and it was also indirectly proportional to the improvement of Human Resources development, 2) Organizational Culture significantly influenced employee performance, thereby making a positive and significant contribution to Human Resources development. 3) Leadership and organizational culture simultaneously impacted performance of workers.